A PROFILE OF PRIVATE SCHOOLS IN QUEBEC - Magnuson, Roger (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1993)
Quebec leads the nation in the percentage of its school-age population in private schools. Among other reasons, the popularity and strength of private education in the province can be attributed to an historical tradition that is measured in centuries, parental dissatisfaction with public education, and a Liberal scheme of government funding. At the same time, there is a continuing debate over government aid to private schools. Critics charge that government assistance is tantamount to a misuse of public funds. RÉSUMÉ Le Québec se classe en tête de toutes les provinces pour ce qui est du pourcentage de la population d’âge scolaire qui fréquente l’école privée. La popularité et le dynamisme de l’enseignement privé dans la province sont attribuables à une tradition historique qui remonte à plusieurs siècles, au mécontentement des parents vis-à-vis de l’enseignement public et à un régime de financement gouvernemental assez libéral. En même temps, le débat se poursuit sur l’aide de l’État aux écoles privées. Les critiques soutiennent que cette aide équivaut à un détournement des deniers publics.